BASIC SCHOOL AS THE IMPORTANT STAGE OF FORMING OF INFORMATIVE SPECIALIST`S COMPETENCE - Efimenko, B.C. (Journal of Information Technologies in Education (ITE), 2010)
The following article deals with a problem of forming of informative pupil’s competence.